Current Status of Assistive Technology for AAC for People with Autism Spectrum Disorders in Nepal - Shrestha, Sachin; Shah, Amit (SCITECH Nepal, 2020)
This paper is focussed on the current status of usage of assistive technology for augmentative and alternative communication (AAC) for the person with autism spectrum disorder (ASD) in Nepal. ASD is marked by core features including impaired social communication, and restrictive and repetitive behaviours and interest (Diagnostic and Statistical Manual of Mental Disorders 5th Edition: DSM 5). AAC is a specific type of assistive technology that can benefit person with autism (PWA) of all ages by promoting independence, expanding communication and increasing social interactions. The major objective of this paper is to analyse the current status of AAC assistive technology for person with autism (PWA) in Nepal. The paper first analysed the assistive technology in general and then is inclined toward the current status of its development in Nepal. The research methodology of the paper included interviews and discussion sessions. The data were further reviewed based on the reports from the relevant organizations and learning outcomes from different autism related trainings and workshops. The authors visited various organizations related to autism in Nepal, Autism Care Nepal Society (ACNS) and Special School for Disability and Rehabilitation Center (SSDRC) and carried out interviews and discussions and also participated in various autism related training sessions and workshops. The findings of this paper showed that despite the high prevalence rate of autism, there is very less progress in managing ASD in Nepal and that the usage of assistive devices is limited to low tech only.